2007
DOI: 10.2176/nmc.47.70
|View full text |Cite
|
Sign up to set email alerts
|

Venous Aneurysm Development Associated With a Dural Arteriovenous Fistula of the Anterior Cranial Fossa With Devastating Hemorrhage-Case Report-

Abstract: A 67-year-old man presented with devastating intracranial hemorrhage (ICH) from an anterior cranial fossa dural arteriovenous fistula (DAVF). Four years earlier, digital subtraction angiography had disclosed a DAVF at the right anterior cranial fossa fed mainly by the ethmoidal branches of the bilateral sphenopalatine arteries and slightly by the ethmoidal arteries of the bilateral ophthalmic arteries, and drained primarily by the sphenoparietal and cavernous sinuses via two dilated cortical veins and slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Haemorrhage results from rupture of the fragile parenchymal veins which had become arterialised as a result of the cortical venous reflux and hypertension. This is commoner in the presence of venous aneurysm and drainage of DAVF into the deep venous sinuses as in our case 10 13. Our patient presented acutely with intraparenchymal haemorrhage and with features of raised intracranial pressure such as sudden headache, visual abnormality, disturbance of consciousness and gross hemiplegia.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Haemorrhage results from rupture of the fragile parenchymal veins which had become arterialised as a result of the cortical venous reflux and hypertension. This is commoner in the presence of venous aneurysm and drainage of DAVF into the deep venous sinuses as in our case 10 13. Our patient presented acutely with intraparenchymal haemorrhage and with features of raised intracranial pressure such as sudden headache, visual abnormality, disturbance of consciousness and gross hemiplegia.…”
Section: Discussionsupporting
confidence: 49%
“…A previous series described a 60-year-old man who presented with subarachnoid/intraparenchymal haemorrhage and had right DAVF fed by the right middle meningeal artery (MMA) and associated with aneurysms of the right anterior cerebral and left internal carotid-posterior communicating arteries considered to be remote 3. Hashiguchi et al 10 also demonstrated that the development of venous aneurysm over time may be a part of the natural history of DAVF and significantly contributed to the haemorrhagic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Drainage of these lesions is primarily via pial veins of the anterior frontal lobe into the superior sagittal sinus or posteriorly toward the cavernous sinus, but less frequently through basal veins 1 . Associated venous aneurysm or varix at the venous side of the fistula were common in the reported cases and have been considered to be the source of the intracerebral hemorrhages 1–3 . Hashiguchi et al 3 reported a patient with an anterior cranial fossa DAVF who presented with venous aneurysm development over 4 years and finally suffered catastrophic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…DAVF of the anterior fossa have an extraordinary high risk of hemorrhage, which was thought to be related to the distinct pattern of venous drainage 1–5 . Drainage of these lesions is primarily via pial veins of the anterior frontal lobe into the superior sagittal sinus or posteriorly toward the cavernous sinus, but less frequently through basal veins 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Imaging follow-up could include serial angiograms to identify changes associated with aggressive behavior, such as the development of new fistula sites, increased arterial flow, venous engorgement, venous aneurysms, or dural sinus stenosis. 11,21,33,50 In addition, MR imaging studies could be used to monitor for the development of signal changes on T2 or FLAIR that might indicate subclinical ischemic changes secondary to venous hypertension. Perfusion imaging using CT or MR could also be considered given the wide availability of these tools.…”
Section: Treatmentmentioning
confidence: 99%